Comparative study between intramyometrial oxytocin and oxytocin analogue (carbetocin) in prevention of postpartum hemorrhage following cesarean section - Farid A Kassab; Abd E.A Sedek (Wolters Kluwer Medknow Publications, 2021)
Background and aim This is a prospective randomized single-center study aimed to assess the efficacy of carbetocin versus intramyometrial oxytocin in the prevention of atonic postpartum hemorrhage following Cesarean section in high-risk women. Patients and methods A total of 160 women with gestational age more than 38 weeks at high risk for primary atonic postpartum hemorrhage undergoing elective or urgent cesarean section under regional or general anesthesia were randomly divided into two equal groups: group A included 80 patients, and they received oxytocin 20 IU intramyometrially. Group B included 80 patients, and they received carbetocin, 100 μg intravenously. Results There was no significant difference in the mean values of hematocrit before and 24 h after delivery (P>0.05). Similarly, there was no significant difference in the estimated blood loss calculated by hematocrit values (P>0.05). Moreover, it was shown that 17.5% of women in the carbetocin group needed additional uterotonics versus 25% of women in the oxytocin group. Therefore, there was no significant difference between both groups regarding needing additional uterotonics. There were eight cases that needed more surgical intervention. Conclusion Both drugs are equally effective in prevention of atonic postpartum hemorrhage. There is no significant difference between single injection of carbetocin and intramyometrial 20 IU oxytocin in reducing the use of additional oxytocic agents.